Pelatihan Pembuatan Story Maps Untuk Meningkatkan Pemahaman Bencana Longsor dan Upaya Mitigasinya di Kota Semarang - Puji Hardati; Dewi Liesnoor Setyowati; Eva Banowati (Universitas Negeri Semarang, 2025)
Story Maps is a web-based Geographic Information System (GIS) application. Disasters are considered normal and do not necessarily happen, for this reason it is necessary to increase knowledge, attitudes and behavior regarding disasters. The general objective of the activity is to assist training in making Story Maps for landslide-prone disasters in disaster mitigation efforts. The specific objectives of the activity are: 1) analyzing the use of Story Maps for disaster awareness, 2) landslide disaster mitigation training, 3) analyzing understanding of landslide disaster preparedness. Community service activities are carried out together with MGMP IPS Education partners in Semarang City. The solutions offered by universities are: 1) transferring knowledge by holding training for mentoring, coaching and strengthening capacity to have a disaster care attitude, 2) providing assistance so that they are able to innovate and be creative in landslide disaster preparedness activities, 3) implement the ability to develop programs landslide disaster preparedness activities. The expected results are: educational training modules for landslides, strengthening MGMP capacity in terms of knowledge, attitudes and behavior regarding disaster care, innovation strategies for disaster care activities.